Religia - o valoare substitut? - Lotreanu, Nicolae (Calitatea Vieții, 1994)
Though the place of the religion immediately after family and labour may suggest a religions resurgence, l am proposing another hypothesis for explaining their situation, based on these fundamental facts: the uncommon social experiences lived during communism are focussing the options of the Romanians around a substitute value due to the accumulation of five processes already started during the Old Regime: the antireligion policy herself; the resurgence of the nationalism; the roles of the family within the socialisation process; the emergence of an introverted spiritual environment as a mean of facing the ideological pressions; the individual identity crise, especially within the aged groups.